2023
DOI: 10.1186/s11658-023-00464-7
|View full text |Cite
|
Sign up to set email alerts
|

CKM and TERT dual promoters drive CRISPR–dCas9 to specifically inhibit the malignant behavior of osteosarcoma cells

Abstract: Improvements in treatment and chemotherapy have increased the survival rate of osteosarcoma, but overall efficacy remains low, highlighting the need for new gene therapy methods. Clustered regularly interspaced short palindromic repeats–deactivated Cas9 (CRISPR–dCas9) technology offers a promising strategy, but targeting osteosarcoma cells precisely is a challenge. We designed a system to achieve specific expression of CRISPR–dCas9–KRAB in osteosarcoma cells by using the creatine kinase muscle (CKM) promoter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Meanwhile, an opposite trend was observed in the interference group compared with the NC-siRNA group ( Figures 2K – P ). The differentiation and development of myoblasts into multinucleated myotubes is controlled at multiple levels by a number of key transcription and regulatory factors ( 24 ). The CKM and myogenesis regulatory factors ( MYFs ) family of genes play important regulatory roles in initiating and maintaining the process of skeletal myoblast differentiation and are considered to be hallmark factors that promote myoblast differentiation ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, an opposite trend was observed in the interference group compared with the NC-siRNA group ( Figures 2K – P ). The differentiation and development of myoblasts into multinucleated myotubes is controlled at multiple levels by a number of key transcription and regulatory factors ( 24 ). The CKM and myogenesis regulatory factors ( MYFs ) family of genes play important regulatory roles in initiating and maintaining the process of skeletal myoblast differentiation and are considered to be hallmark factors that promote myoblast differentiation ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…These researchers fused the dCAS9 protein with the KRAB fusion protein, a transcriptional repressor domain that can silence gene expression. The CKM and TERT promoters drive the expression of dCas9-KRAB and the sgRNA in malignant OS cells, explicitly targeting the MDM2 proto-oncogene [31]. The study found that the CRISPR-dCAS9-KRAB system could specifically target and silence the MDM2 gene.…”
Section: Proto-oncogenes In Osteosarcomamentioning
confidence: 93%
“…Another gene therapy approach for treating OS is to target tumor-associated protooncogenes and silence their expression to inhibit tumor growth [31]. Proto-oncogenes that can become abnormally activated in OS include MDM2, SAS and c-myc [31].…”
Section: Proto-oncogenes In Osteosarcomamentioning
confidence: 99%
See 2 more Smart Citations